2009
DOI: 10.1007/s10439-009-9759-1
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Noninvasive Blood Pressure Measurement: A Novel Modeling Methodology of the Relationship Between Blood Pressure and Pulse Wave Velocity

Abstract: In this paper, we aim to establish a new mathematical model that relates pulse wave velocity (PWV) to blood pressure (BP) for continuous and noninvasive BP measurement. For the first time, we derive an ordinary differential equation (ODE) expressing the fundamental relation between BP, elastic modulus G and PWV. The general solution of this ODE is the mathematical BP-PWV model. In our model, the elastic modulus G is included in model parameters, unlike the existing theoretical models. This enables us to expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 11 publications
(29 reference statements)
1
69
1
Order By: Relevance
“…Similar nonlinear relations between BP and brachial-ankle PWV were described by Yamashina et al 2003 in human beings. Other authors obtained a non-linear relationship between PVW and BP, which was inverted to that of the above cited studies (Chen et al 2009;Zheng and Murray 2009). Linear as well as non-linear PTT-BP functions have been described in isolated canine common carotid arteries (Callaghan et al 1984), while a number of authors reported linear relations (Geddes et al 1981;Payne et al 2006).…”
Section: Discussionmentioning
confidence: 80%
“…Similar nonlinear relations between BP and brachial-ankle PWV were described by Yamashina et al 2003 in human beings. Other authors obtained a non-linear relationship between PVW and BP, which was inverted to that of the above cited studies (Chen et al 2009;Zheng and Murray 2009). Linear as well as non-linear PTT-BP functions have been described in isolated canine common carotid arteries (Callaghan et al 1984), while a number of authors reported linear relations (Geddes et al 1981;Payne et al 2006).…”
Section: Discussionmentioning
confidence: 80%
“…Ears, toes and fingers are common sites used for measurement [60]. PTT f measured from the foot of one PPG to that of another has been demonstrated to have a strong correlation to invasive DBP [61], but a study on 44 normotensive male subjects concluded otherwise [62]. The peaks of PPG that theoretically represent SBP have been found to be unreliable indicators of SBP.…”
Section: Pulse Transit Time (Ptt)mentioning
confidence: 99%
“…The logarithmic model Equation (6) approaches negative infinity as "Time Delay" tends to zero, making it difficult to use this relationship to represent small BP [61].…”
Section: Logarithmic Modelmentioning
confidence: 99%
“…We previously proposed a BP-PWV model and validated it with DBP measurements from a small population of subjects with no evidence of cardiovascular disease. 8 PWV d was determined by the commonly used foot-tofoot method. However, we previously felt difficult to determine proper PWV s because the shape of the pulse wavecrest changed unpredictably due to various influencing factors.…”
Section: Introductionmentioning
confidence: 99%